The Fleas (Siphonaptera) in Iran: Diversity, Host Range, and Medical Importance - Maleki-Ravasan, N.; Solhjouy-Fard, S.; Beaucournu, J-C; Laudisoit, A.; Mostafavi, E. (Public Library of Science, 2017)
Flea-borne diseases have a wide distribution in the world. Studies on the identity, abundance, distribution and seasonality of the potential vectors of pathogenic agents (e.g. Yersinia pestis, Francisella tularensis, and Rickettsia felis) are necessary tools for controlling and preventing such diseases outbreaks. The improvements of diagnostic tools are partly responsible for an easier detection of otherwise unnoticed agents in the ectoparasitic fauna and as such a good taxonomical knowledge of the potential vectors is crucial. The aims of this study were to make an exhaustive inventory of the literature on the fleas (Siphonaptera) and range of associated hosts in Iran, present their known distribution, and discuss their medical importance.